INFERTILITY AND IVF PREGNANCY: A CROSS-SECTIONAL STUDY AMONG NORTH INDIAN WOMEN - POOJA SINHA; NISHA MALIK; RAVISHEKAR N HIREMATH; VIVEK GUPTA; NAMITA BATRA; FLORIKA DAS; PRIYANKA PATEL (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objective: The aim of the study is to compare the reproductive, perinatal, and neonatal outcomes among women conceived by in vitro fertilization to those females conceived spontaneously. Methods: It is an observational descriptive cross-sectional study. The data were collected for 1 year and 6 months. The study population consisted of 82 term females admitted under the Department of Obstetrics and Gynecology of the hospital nearing termination who conceived after infertility. A semi-structured pre-designed questionnaire was used to collect the data. Results: There was a significant difference in the mean age at conception of the patients who conceived spontaneously versus those who conceived after infertility treatments (p<0.001). The rate of cesarean section was higher in the group with a history of infertility (75%) with the rate being 35.7% in the spontaneous conception group (p=0.038). The neonatal outcomes were not significantly different in the two groups. Conclusion: There is a need to analyze and compare patients on a larger scale, so as to decide if special algorithms are required to treat pregnancies conceived after infertility treatments.